Cash for care and care employment: (Missing) debates and realities. (17th April 2019) - Da Roit, Barbara; Moreno‐Fuentes, Francisco Javier
Abstract: The introduction of cash‐for‐care (CfC) schemes in different European countries over the last years has responded to a plurality of strategies aimed at attending the rising demand and increasing costs of the long‐term care needs of an ageing population. The specific system of care provision in each country shaped the response given to those challenges, as well as the room for manoeuvre for policymakers when trying to transform the domain of care into a sphere where markets may play a larger role, partly relieving families, and also the state, from these responsibilities. Policy debates and scholarly analyses largely overlooked the contribution of these schemes to the creation and shaping of employment. This article provides a comparative analysis of how CfC‐based policies entail—alongside the regulation of informal care—a(n implicit or explicit) connection with care employment and may contribute to structuring employment relations in this sector. It looks jointly at the specific features of CfC and at the institutional context—welfare regime—in which they are embedded in order to assess the extent to which these schemes contributed (generally unintendedly) to a transformation of the care employment size and features in seven European countries.